Workload of caregiver according to functionality level of the person with disabilities in a district of Lima - Asencios-Ortiz, Rocio del Pilar (2019)
Introduction. According to the National Institute of Statistics and Informatics (INEI), in 2017 there were three million people with disabilities in our country. Of these, 5% have a significant functional limitation, so they have to require a caregiver; who can see affected his physical and emotional activity, and eventually, they get sick. Objective. To establish the relationship between the burden of the caregiver and level of functionality of the person with disabilities. Methods. 50 caregivers and 50 people with disabilities were included. The Functional Independence Measure (FIM) is an accepted instrument for measuring disability, in three categories: complete dependence, relative dependence and independence. The Zarit and Zarit Test measures the burden of caregiver; classifying it into three categories: absence of burden, light burden and intense burden. Results. The majority of caregivers of people with disabilities reported having an intense burden, this being greater when caring for a person with complete dependence and lower when caring for a person with functional independence. However, no statistically significant association was found. Conclusion. It is common for caregivers with intense burden to be in charge of patients with complete or relative dependence, in people registered in the Comprehensive Care Service for People with Disabilities (SAIPD) of the Instituto Nacional de Bienestar Familiar (INABIF), during the year 2018. Future studies, with a better methodology, could corroborate a possible relationship between these variables.